Using Different Kinds of Activated Carbon for Removing Some Pollutants from Tap Water and Well Water - Faisal, Heba Ghazwan; Al Fatlawy, Yaaroub Faleh (Iraqi Journal of Science, 2026)
Removal of some physical, chemical and biological pollutants from tap water and well water using three different types of activated carbon has been investigated in this research. Water samples were collected from the local area and treated in a closed system(a one-step household filter system), and the turbidity, electrical conductivity, total dissolved solid, chloride, some heavy metals such as lead (Pb), copper (Cu), nickel (Ni) and chromium (Cr), nitrite (NO2), nitrate (NO3) and total plate count has been measured before and after treating of the three types of activated carbon (lignocellulose activated carbon (AC1), anthracite coal activated carbon (AC2) and commercial activated carbon (AC3) which it prepare by chemical activation of the carbonized material and then washed and dried. The results showed the high efficiency of activated carbon in removing turbidity compared to other pollutants where it was in tap water 3.59NTU before filtration then after being filtered using the three types of activated carbon AC1, AC2 and AC3 were 1.18NTU, 1.36NTU and 2.27NTU respectively. Furthermore, turbidity in the well water before being filtered was 5.92NTU, and after filtering with AC1, AC2 and AC3 was 1.14NTU, 0.1 NTU and 2.4NTU, respectively. However, it is different in efficiency according to the type of activated carbon and the pollutant type since AC1 has a high efficiency to reduce Pb, and Cu, among others, where it declines from 0.054 ppm, 0.085ppm to 0.042ppm, 0.005ppm respectively for well water. AC3 was effective in lowering Cl, Ni, and Cr and reducing bacterial contamination where it was 283.3mg/l, 0.025ppm, 0.035ppm and 36cell/ml before filtering and 278.6mg/l, 0.011ppm, 0.015 and 27 cell/ml after filtering well water. AC2, which was more effective in adsorption of NH3 from 2.8mg/l to 1.2mg/l in tap water. Each type of activated carbon has shown quite good effects on a particular pollutant making it crucial to determine their application suitably. Although anthracite and animal base activated carbon is rarely used in water treatment, it exhibits quite good results in reducing some pollutants. In general, the adsorption capacity depends on the initial concentration of the sample, agitation speed and contact time.